Pengaruh Pupuk Kandang Sapi dan Inokulan Mikroba Trichoderma sp. terhadap Pertumbuhan dan Hasil Tanaman Caisim (Brassica juncea (L.) Czern) - Fawzy Muhammad Bayfurqon; Nurcahyo Widyodaru Saputro; Miftakhul Bakhrir Rozaq Khamid (Universitas Gunadarma, 2017)
This experiment was conducted at screen house in Ciwaringin village, Lemahabang subdistrict, Karawang district, West Java. This experiment was conducted to find out the best combination of cow manure dosage with Trichoderma sp microbial inoculants in Chinese mustard cultivation.. This experiment used an experimental method by using a randomized block design (RBD) Factorial with two factors. The factors were: cow manure dosage which consists of three levels i.e : D0 (control), D1 (20 g / polybag), D2 (40 g / polybag) and microbial inoculant Trichoderma sp which consists of five levels i.e K0 (0 g), K1 (5 g), K2 (10 g), K3 (15 g), K4 (20 g). Treatment was repeated three replications so there are 45 experimental units. The results showed there was a real effect on their own dosage of cow manure to the plant height, leaf area index, plant fresh weight and the weight of marketable crops. Microbial inoculant Trichoderma sp. treatment showed a real effect independently on the number of leaves. Cow manure dosage in treatment D2 gives the best results andsignificantly different from the other treatment on plant height, leaf area index, the weight of fresh plants and plant weight of marketable sequentially reach 27.01 cm, 166.56. cm2, 54.60 g / plants, and 47.84 g / plant. Microbial inoculant Trichoderma sp. in treatment K1 gives the best results with 4.59 leaves, and significantly different to the treatment K0, K3 and K4